Idarucizumab for dabigatran reversal in cardiac tamponade complicating percutaneous intervention in ST elevation myocardial infarction - Kurdziel, Marta; Hudzik, Bartosz; Kazik, Anna; Piegza, Jacek; Szkodzinski, Janusz; Gąsior, Mariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
An 83-year-old man with a history of permanent atrial fibrillation (AF) anticoagulated by dabigatran 150 b.i.d., type 2 diabetes mellitus, and hypertension was admitted to the hospital with a diagnosis of ST-elevation myocardial infarction (STEMI). The patient was loaded with 300 mg of aspirin p.o., 5000 IU of unfractionated heparin i.v. and 600 mg of clopidogrel and was transferred to the catheterization laboratory. Coronary angiography demonstrated left anterior descending artery (LAD) occlusion. During the LAD angioplasty a dissection of a distal part of the LAD and the blood extravasation to the pericardium occurred (Figure 1 A). Idarucizumab 2 × 2.5 g i.v. was administered and the inflated balloon maintained at the site of coronary perforation. About 10 min after the end of idarucizumab infusion, the balloon was deflated and the patient presented with clinical symptoms of cardiac tamponade such as blood pressure decrease and tachycardia. The echocardiographic assessment revealed up to 16 mm accumulation of pericardial fluid (Figure 2 A). Immediately the covered stent was implanted (Papyrus, Biotronik) and the pericardiocentesis was carried out. 320 ml of blood was finally drained. Control contrast injection revealed a covered perforating zone with no contrast extravasation (Figure 1 B). The echocardiographic control revealed pericardial effusion less than 5 mm (Figure 2 B). The patient was stable with a blood pressure of 130/80 mm Hg, a heart rate of 100–130/min (AF), and without chest pain. No significant reduction in the red blood cell count was observed. Antiplatelet therapy was given consisting of aspirin and clopidogrel. In the following days enoxaparin was introduced and finally changed to dabigatran 110 mg b.i.d.